The Visit Intention of New York City: The Influence of Social Media Marketing (Study on Tourist Who Wish Visit The New York City) - Ghassani Herstanti (Return : Study of Management, Economic and Bussines, 2023)
The largest market in the US for overseas visitors, who often stay longer and spend more, is New York City. Depending on past tourist behavior, there are two approaches that should be taken when promoting New York City (NYC) as a destination. When promoting a destination to tourists who have already been there before, the emphasis should be on updating them on new information and luring them back. The purpose of this study is to examine the effects of social media marketing initiatives, destination image, attitude, awareness, and perceived value on visit intention to New York City. The SEM-PLS approach was employed in this study's data analysis. 42 travelers who intended to visit New York City filled out a 1–5 scale questionnaire that was used to obtain the data. Ten theories pertaining to the 6 factors under investigation were put up. The study's findings indicate that Social Media Marketing Activity has no relationship with the Destination Image, Destination Attitude, Destination Awareness and Perseced Value variables. While the variables that have a relationship with Visit Intention New York City are Destination Awareness and Perceived Value. This study has consequences for giving tourists who want to visit New York City an overview and an explanation.